2020
DOI: 10.2340/20030711-1000035
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy effectively decreases the frequency of joint bleeding improves joint health and reduces pain in hemophilic elbow arthropathy: A prospective cohort study

Abstract: Objective: To verify the safety and effectiveness of manual therapy intervention using fascial therapy in adult patients with haemophilic elbow arthropathy. Methods: Prospective cohort study. A total of 28 patients with haemophilic elbow arthropathy was recruited in 3 cities in Spain. Patients received onefascial therapy session per week for 3 weeks. The dependent variables were: frequency of joint bleeding, joint pain (visual analogue score) and joint status (Hemophilia Joint Health Score). Outcomes were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although the use of manual therapy in haemophilia is increasing, most of the studies have focused on the lower extremities with regard to mobility 7‐11 . The limited number of studies on manual therapy of the elbow joint has found in the literature 4,12,13 . However, with the increase in life expectancy of haemophilia patients, labour force participation, upper limb functionality and independent daily life have become current issues, and elbow is one of the main joints for these.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of manual therapy in haemophilia is increasing, most of the studies have focused on the lower extremities with regard to mobility 7‐11 . The limited number of studies on manual therapy of the elbow joint has found in the literature 4,12,13 . However, with the increase in life expectancy of haemophilia patients, labour force participation, upper limb functionality and independent daily life have become current issues, and elbow is one of the main joints for these.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] The limited number of studies on manual therapy of the elbow joint has found in the literature. 4,12,13 However, with the increase in life expectancy of haemophilia patients, labour force participation, upper limb functionality and independent daily life have become current issues, and elbow is one of the main joints for these. In addition, the elbow joint may prone to complications such as heterotopic ossification and stiffness.…”
Section: Introductionmentioning
confidence: 99%